Sumoylation-independent activation of Calcineurin-NFAT-signaling via SUMO2 mediates cardiomyocyte hypertrophy - Bernt, Alexander; Rangrez, Ashraf Y.; Eden, Matthias; Jungmann, Andreas; Katz, Sylvia; Rohr, Claudia; Müller, Oliver J.; Katus, Hugo; Sossalla, Samuel Tobias; Williams, Tatjana; Ritter, Oliver; Frank, Derk; et al. (Scientific reports, 2016)
The objective of this study was to identify unknown modulators of Calcineurin (Cn)-NFAT signaling. Measurement of NFAT reporter driven luciferase activity was therefore utilized to screen a human cardiac cDNA-library (~107 primary clones) in C2C12 cells through serial dilutions until single clones could be identified. This extensive screening strategy culminated in the identification of SUMO2 as a most efficient Cn-NFAT activator. SUMO2-mediated activation of Cn-NFAT signaling in cardiomyocytes translated into a hypertrophic phenotype. Prohypertrophic effects were also observed in mice expressing SUMO2 in the heart using AAV9 (Adeno-associated virus), complementing the in vitro findings. In addition, increased SUMO2-mediated sumoylation in human cardiomyopathy patients and in mouse models of cardiomyopathy were observed. To decipher the underlying mechanism, we generated a sumoylation-deficient SUMO2 mutant (ΔGG). Surprisingly, ΔGG replicated Cn-NFAT-activation and the prohypertrophic effects of native SUMO2, both in vitro and in vivo, suggesting a sumoylation-independent mechanism. Finally, we discerned a direct interaction between SUMO2 and CnA, which promotes CnA nuclear localization. In conclusion, we identified SUMO2 as a novel activator of Cn-NFAT signaling in cardiomyocytes. In broader terms, these findings reveal an unexpected role for SUMO2 in cardiac hypertrophy and cardiomyopathy, which may open the possibility for therapeutic manipulation of this pathway.
Gesehen am 07.05.2020